Semente Crioula (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Semente Crioula is a dramaturgy developed from a travel journal written during the Interdisciplinary Experience Internship (Estágio Interdisciplinar de Vivência) with Via Campesina in western Santa Catarina, in 2025. Influenced by Clarice Lispector’s Água Viva, the work weaves together intimate experiences and political and social issues related to land conflict. The narrative of Doralice, a hybrid figure between human and animal, highlights territorial disputes and reflections on the body, nature, and self-appropriation.
Keywords: land conflict; memory; sensitive dramaturgy